1993
DOI: 10.1038/ng0193-73
|View full text |Cite
|
Sign up to set email alerts
|

The molecular basis of the human serum paraoxonase activity polymorphism

Abstract: The organophosphate cholinesterase inhibitor paraoxon is hydrolysed by serum paraoxonase/arylesterase. A genetic polymorphism of paraoxonase (PON) activity which determines high versus low paraoxon hydrolysis in human populations, may determine sensitivity to parathion poisoning. We demonstrate that arginine at position 192 specifies high activity PON whereas a glutamine specifies the low activity variant. Allele-specific probes or restriction enzyme analysis of amplified DNA allow for the genotyping of indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
554
3
14

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 771 publications
(583 citation statements)
references
References 37 publications
12
554
3
14
Order By: Relevance
“…26,27 Briefly, (a) the CÀ108T SNP was amplified using primers GACC GCAAGCCACGCCTTCTGTGCACC and TGCAGCCG CAGCCCTGCTGGGGCAGCGCCGATTGGCCCGCCGC with 5% DMSO and an annealing temperature of 631C for 35 cycles. The 109 bp fragment was digested with BstUI, yielding 67 and 42 bp fragments in the presence of the C allele.…”
Section: Genotypingmentioning
confidence: 99%
See 2 more Smart Citations
“…26,27 Briefly, (a) the CÀ108T SNP was amplified using primers GACC GCAAGCCACGCCTTCTGTGCACC and TGCAGCCG CAGCCCTGCTGGGGCAGCGCCGATTGGCCCGCCGC with 5% DMSO and an annealing temperature of 631C for 35 cycles. The 109 bp fragment was digested with BstUI, yielding 67 and 42 bp fragments in the presence of the C allele.…”
Section: Genotypingmentioning
confidence: 99%
“…26,27 Paraoxonase is the serum enzyme physiologically involved in protecting low-density lipoproteins (LDL) and high-density lipoproteins (HDL) from oxidation, and is responsible for OP inactivation in humans. 28,29 The three SNPs assessed here are the best-characterized functional polymorphisms affecting either the amount of serum paraoxonase or its affinity for specific substrates, ultimately leading to impressive interindividual differences in human serum paraoxonase activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum PON1 activity is influenced by environmental and genetic factors and varies among individuals in all populations. These variations in PON1 activity are mainly related to the expression of two polymorphisms located in the coding regions of the PON1 gene; Q192R (Q: glutamine, R: arginine) and L55M (L: leucine, M: methionine) [1,9,13,17,23,27]. Subsequent studies on polymorphisms contained in the promoter region of the PON1 locus have shown that the polymorphism located in the promoter region T(-107)C has a dominant effect on PON1 gene expression and enzymatic activity [5,14,22].…”
Section: Introductionmentioning
confidence: 99%
“…This variability is attributed to environmental factors, such as smoking, diet, alcohol consumption, but also to the genetic polymorphisms in the PON1 gene. There are two annotated missense SNPs within the PON1 coding region: p.L55M (rs854560), where the major allele L leads to elevated PON1 protein levels, and p.Q192R (rs662), affecting substrate specificity as well as enzyme activity (Garin et al 1997;Humbert et al 1993). These two missense polymorphisms affect also the ability of HDL to protect LDL from oxidative modifications, with MM/QQ genotype being most effective (Mackness et al 1998a).…”
Section: Introductionmentioning
confidence: 99%